Growing and Handling of Bacterial Cultures 2019
DOI: 10.5772/intechopen.76282
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenemases

Abstract: Carbapenems are usually regarded as the last treatment option for serious infections caused by Gram-negative and Gram-positive microorganisms. Although they are stable to hydrolysis by most β-lactamases, their usage as the last resort antbiotics was seriously compromised by the appearance of carbapenemhydrolyzing enzymes called carbapenemases. These enzymes are produced mostly by Enterobacteriaceae and Gram-negative nonfermentative bacteria such as Pseudomonas aeruginosa and Acinetobacter baumannii. True carba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 99 publications
0
4
1
Order By: Relevance
“…PAmpC positive isolates in the present study were sensitive to meropenem, imipenem, and Tigecycline 89.5%, 84.2% and 68.4%. These results disagreed with other study conducted by Bedenić et al [27] reported higher susceptibility to Tigecycline and carbapenems (100%). Another study by Manoharan et al [21] reported higher sensitivity 99% for Tigecycline and 97% for imipenem and meropenem.…”
Section: Discussioncontrasting
confidence: 99%
“…PAmpC positive isolates in the present study were sensitive to meropenem, imipenem, and Tigecycline 89.5%, 84.2% and 68.4%. These results disagreed with other study conducted by Bedenić et al [27] reported higher susceptibility to Tigecycline and carbapenems (100%). Another study by Manoharan et al [21] reported higher sensitivity 99% for Tigecycline and 97% for imipenem and meropenem.…”
Section: Discussioncontrasting
confidence: 99%
“…Although they are stable to hydrolysis by most β-lactamases, their usage as the last resort antibiotics was seriously compromised by the appearance of new class of bacterial enzymes capable of inactivating carbapenems, called as carbapenemases. 28 Resistance to carbapenem antimicrobials is either due to expression of carbapenemases or due to combined mechanisms of resistance (overexpression of broad-spectrum β-lactamases together with efflux pumps, impermeability); however, carbapenemases production represents the most important mechanism of resistance in Enterobacteriaceae, associated with multi-or pan-drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The Ambler classification system has classified carbapenemases into four groups, three of which (A, B and D) belong to Enterobacteriaceae ( Hall and Barlow, 2005 ). A Class C carbapenemases have also been described; however, they are not considered true carbapenemases as they have a low enzyme’s catalytic efficiency and a permeability defect, which only gives them a slight reduction in susceptibility to carbapenems ( Bedenić and Sardelić, 2018 ). Class A carbapenemases are associated with K. pneumoniae (KPC) as are the less common non-metallocarbapenemase type A (NMC-A) and SME enzymes; Class B carbapenemases are associated with metallo-β-lactamases (MBL) including New Delhi metallo-β-lactamases (NDM), the IMP family of carbapenemases, and the Verona integron–encoded metallo-β-lactamases (VIM).…”
Section: Antimicrobial Resistance Of Staphylococcus Aureusmentioning
confidence: 99%